Antimicrobial effect of cell-free supernatant of Lactobacillus against isolated Candida Spp. - Khairi Jameel Al-Ruaby; Mahasin Turkey Shaker (Genius Journals, 2022)
Antimicrobial activity of the cell free culture supernatants (CFCS) was tested against the . C.albicans and C. Parapsilosis . the Zones of inhibition of probiotic (Lactobacillus) against concentrations. Regarding L. acidophilus, the 7 EPEC were compared among 105,106,10 concentration. L. plantarum , the best zone of best zone of inhibition was obtained at 106 concentration. While the best inhibition zone of L. 7 inhibition was obtained at 10 concentration and the Zones of inhibition of probiotic was obtained at 106 rhamnosus concentrations. 7 (Lactobacillus) against EAEC was compared among 105 , 106 and 10 concentration. In 7 Regarding L. acidophilus, the best zone of inhibition was obtained at 10 concentration. The he best zone of inhibition was obtained at 106 case of L. plantarum, t L. rhamnosus. The best zone of inhibition was obtained at the concentration 106 Characterization of antimicrobial substances produced by Lactobacillus has been studded The result showed the bacteriocin only has inhibitory effect against pathogenic E. coli .
Keywords: Albicans and C; Parapsilosis; Probiotic; Lactobacillus spp